Research agendas and culture: a new approach to analysing the academic profession in Asia and Europe - Santos, J. M. (2022)
This paper investigates the research agendas of academics in Asia and Europe with reference to cultural differences between the two continents. Unlike studies on the influence of culture on research that focus on only one or a few countries, this study explores the relationship between cultural dimensions and research agendas at the continental level, across Europe and Asia. The study uses general linear modelling with interaction terms to identify how cultural dimensions influence research agendas and how their influence differs between Europe and Asia. Hofstede’s cultural dimensions model and the Multidimensional Research Agendas Inventory-Revised scale are adopted in this study, as measures of cultural aspects and research agenda-setting, respectively. The results show that culture influences several aspects of research agenda-setting in both Asia and Europe, but these dynamics are not always identical across continents. These findings are relevant both for academics studying the cultural dynamics of science, and also for policy-makers who need to consider these cultural aspects while striving to promote specific research agendas.